Management of Twin Pregnancies With Short Cervix in a Single System [5L]. (May 2017) - Buchanan, Christopher; Hostetter, Sarah; Volkman, Emma; Miller, Collin; Gavard, Jeffrey; Vricella, Laura K.
Abstract : INTRODUCTION: We aimed to evaluate whether twin pregnancies with cervical length ⩽25 mm who received cerclage had different rates of preterm birth (PTB) < 32 weeks compared with other forms of management. METHODS: This is a retrospective cohort of twin pregnancies with a cervical length ⩽25 mm at 14w0d-27w6d at our academic center (2013-2016). Twin pregnancies with short cervix were eligible for 4 types of management: cerclage, Inflatoball cervical pessary (pessary), vaginal progesterone (VP), or expectant management (EM). Data were analyzed on intent-to-treat basis. Primary outcome was delivery < 32 weeks. Secondary outcome was interval from diagnosis of short cervix to delivery. RESULTS: 60 patients met criteria for analysis: cerclage (n=19), pessary (n=11), VP (n=11), EM (n=19). Age, race, parity and history of PTB were similar among groups. Group and pairwise comparisons showed similar rates of delivery < 32 weeks for all groups (58% cerclage, 36% pessary, 55% VP, 47% EM; P=0.7). Survival analysis was used to evaluate the interval from diagnosis to delivery, showing similar intervals when comparing all 4 interventions as a group, but pairwise comparison demonstrated greater median interval for cerclage vs EM (61.7 vs 55.0 days; P=0.04) and for VP vs pessary (65.0 vs 48.8 days; P=.01). CONCLUSION: No difference in delivery < 32 weeks was found in this cohort of twin pregnancies with cervical length ⩽25 mm who underwent different management. Patients receiving a cerclage had a longer interval to delivery compared to expectant management. Randomized controlled trials are needed to determine the optimal management of twin pregnancies with short cervix.